In vitro approach to evaluate the fermentation pattern of inulin-rich food in obese individuals. Issue 4 (14th November 2019) - Kalala, Gaétan; Kambashi, Bienvenu; Taminiau, Bernard; Schroyen, Martine; Everaert, Nadia; Beckers, Yves; Richel, Aurore; Njeumen, Patrick; Pachikian, Barbara; Neyrinck, Audrey M.; Hiel, Sophie; Rodriguez, Julie; et al.
Abstract: Alterations of the gut microbiome have been associated with obesity and metabolic disorders. The gut microbiota can be influenced by the intake of dietary fibres with prebiotic properties, such as inulin-type fructans. The present study tested the hypothesis that obese individuals subjected for 12 weeks to an inulin-enriched v . inulin-poor diet have differential faecal fermentation patterns. The fermentation of cellulose and inulin hydrolysates of six different inulin-rich and inulin-poor vegetables of both groups was analysed in vitro on faecal inocula. The results showed that the microbiota from obese patients who received a fructan-rich diet for 3 weeks produces more gas and total SCFA compared with the microbiota taken from the same individuals before the treatment. Obese individuals fed with a low-fructan diet produce less gas and less SCFA compared with the treated group. The present study highlighted profound changes in microbiota fermentation capacity obtained by prebiotic intervention in obese individuals, which favours the production of specific bioactive metabolites.